Pulmonary endarterectomy in the elderly: safety, efficacy and risk factors. Issue 2 (February 2016) - Vistarini, Nicola; Morsolini, Marco; Klersy, Catherine; Mattiucci, Gabriella; Grazioli, Valentina; Pin, Maurizio; Ghio, Stefano; D'Armini, Andrea Maria
Abstract : Aims: Pulmonary endarterectomy (PEA) is the treatment of choice for patients with chronic thromboembolic pulmonary hypertension, but there are few data in the literature about the results of this procedure in the elderly. In this study, we aimed to assess whether this type of surgery is effective and well tolerated for the elderly. Methods: A total of 264 consecutive patients who underwent PEA between January 2008 and December 2012 were reviewed. PEA was performed under cardiopulmonary bypass and hypothermic ventricular fibrillation, with the aorta left unclamped. The population was dichotomized according to age into the following two groups: below 70 years ( n  = 176, younger patients) and at least 70-year-olds ( n  = 88, elderly patients). Regression models were used to identify predictors of hospital mortality and postoperative adverse events, and their interaction with age was tested. Results: Hospital mortality was slightly, but not significantly higher in elderly patients (9.1 vs. 5.1%; P  = 0.22). Effect modification by history of smoking and preoperative O2 therapy was present. The cumulative survival at 1, 2, and 4 years was 93, 92, and 91% among younger patients; and 88, 86, and 86% among older patients ( P  = 0.19). Clinical and hemodynamic improvement was similar in the two groups. Conclusion: Despite a slightly higher short-term mortality, PEA is feasible and well tolerated for the vast majority of the elderly patients. Clinical and hemodynamic improvements are outstanding, with satisfactory long-term survival rates.